From goods to a good life : intellectual property and global justice - Sunder, Madhavi (Yale University Press, 2012)
In this pioneering book Madhavi Sunder calls for a richer understanding of the effects ofintellectual property law on social and cultural life. Although most scholarship on intellectual property considers this law as it relates to economics, it is first and foremost a tool for promoting innovative products, from iPods to R2D2. More than incentivizing the production of more goods, intellectual property law fundamentally affects the ability of citizens to live a good life. It governs the abilities of human beings to make and share culture, and to profit from this enterprise in a global Knowledge economy. This book turns to social and cultural theory to more fully explore the deep connections between cultural production and human freedom.